2017
DOI: 10.17533/udea.rccp.v30n3a03
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between data mining methods to assess calving difficulty in cattle

Abstract: Comparison between data mining methods to assess calving diffi culty in cattle ¤ Comparación entre métodos de minería de datos para evaluar la difi cultad al parto en ganado AbstractBackground: Dystocia in cattle results in adverse consequences (increased calf morbidity and mortality, decreased fertility, and milk production, lower cow survival and reduced welfare) leading to considerable economic losses. Objective: To classify calvings in dairy cattle according to their diffi culty using selected data mining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Dystocia (birth difficulty) in cows leads to various hostile consequences for the dam and its progeny [ 1 ]. These include increased calf morbidity and mortality, decreased fertility and milk production, low cow survival, health welfare, and economic losses [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dystocia (birth difficulty) in cows leads to various hostile consequences for the dam and its progeny [ 1 ]. These include increased calf morbidity and mortality, decreased fertility and milk production, low cow survival, health welfare, and economic losses [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…CART predictions can be used as an aid to a farmer in the decision-making process regarding herd management [ 8 ]. CART might be used by dairy cattle farmers as a classification model to predict the class of dystocia [ 1 ]. Zaborski et al [ 9 ] indicated that data mining algorithms are useful for discovering dystocia in Polish Holstein Friesian black and white cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of correctly indicated difficult calvings in heifers by RBM was also higher than that diagnosed by QUEST. In the case of heifers (Zaborski et al, 2017), the proportions of correctly identified easy, moderate and difficult calvings on the independent test set by CART were 35.14%, 68.70% and 77.27%. The total accuracy was 60.41%.…”
mentioning
confidence: 97%
“…Only five of the above predictors (SIRE, AGE, HERD, SEX, CLVS) were used for heifers. A detailed description of the dataset is given in Zaborski et al (2016Zaborski et al ( , 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation